9x^-1 = 3(3x-1)
Tìm x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
( 3x - 2 )( 9x2 + 6x + 4 ) - ( 2x - 5 )( 2x + 5 ) = ( 3x - 1 )3 - ( 2x + 3 )2 + 9x( 3x - 1 )
⇔ 27x3 - 8 - ( 4x2 - 25 ) = 27x3 - 27x2 + 9x - 1 - ( 4x2 + 12x + 9 ) + 27x2 - 9x
⇔ 27x3 - 8 - 4x2 + 25 = 27x3 - 1 - 4x2 - 12x - 9
⇔ 27x3 - 4x2 + 17 - 27x3 + 4x2 + 12x + 10 = 0
⇔ 12x + 27 = 0
⇔ 12x = -27
⇔ x = -27/12 = -9/4
(1-3x2)-(x-2)(9x+1)=(3x-4)(3x+4)-9(x+3)2
⇒1-3x2-(9x2+x-18x-2)=9x2-16-9(x2+6x+9)
⇒1-3x2-(9x2-17x-2)= -56x-97
⇒1-3x2-9x2+17x+2=-56x-97
⇒3-12x2+17x=-56x-97
⇒3-12x2+17x+56x+97=0
⇒-12x2+73x+100=0
⇒-(12x2-73x-100)=0
\(\left(2x+3\right)^2+2\left(2x+3\right)\left(x-2\right)+\left(2-x\right)^2=4\)
\(\left(2x+3\right)^2+2\left(2x+3\right)\left(x-2\right)+\left(x-2\right)^2=4\)
\(\left(2x+3+x-2\right)^2=\left(\pm2\right)^2\)
\(\left(3x+1\right)^2=\left(\pm2\right)^2\)
\(\left[\begin{array}{nghiempt}3x+1=2\\3x+1=-2\end{array}\right.\)
\(\left[\begin{array}{nghiempt}3x=2-1\\3x=-2-1\end{array}\right.\)
\(\left[\begin{array}{nghiempt}3x=1\\3x=-3\end{array}\right.\)
\(\left[\begin{array}{nghiempt}x=\frac{1}{3}\\x=-1\end{array}\right.\)
***
\(\left(x+3\right)\left(3-x\right)=5\)
\(3^2-x^2=5\)
\(x^2=9-5\)
\(x^2=4\)
\(x^2=\left(\pm2\right)^2\)
\(x=\pm2\)
***
\(\left(3x+1\right)\left(9x^2-3x+1\right)=2\)
\(27x^3+3=2\)
\(27x^3=2-3\)
\(\left(3x\right)^3=-1\)
\(3x=-1\)
\(x=-\frac{1}{3}\)
a)
(3x+1)^2 -9x (x-1) =46
9x2+6x+1-9x2+9x = 46
15x+1=46
15x=45
x=3
b)
5x (x-3) = 7 (3-x)
5x ( x - 3 ) - 7 ( 3 - x ) = 0
5x ( x - 3 ) + 7 ( x - 3 ) = 0
(5x + 7 ) ( x - 3 ) = 0
5x+7=0 hoặc x-3 = 0
5x=-7 hoặc x=3
x= -7 / 5 hoặc x=3
a: Ta có: \(\left(x+2\right)\left(x+3\right)-\left(x-2\right)\left(x+5\right)=6\)
\(\Leftrightarrow x^2+5x+6-x^2-3x+10=6\)
\(\Leftrightarrow2x=-10\)
hay x=-5
b: Ta có: \(\left(3x+2\right)\left(2x+9\right)-\left(x+2\right)\left(6x+1\right)=\left(x+1\right)-\left(x-6\right)\)
\(\Leftrightarrow6x^2+27x+4x+18-6x^2-x-12x-2=x+1-x+6\)
\(\Leftrightarrow18x+16=7\)
hay \(x=-\dfrac{1}{2}\)
c: Ta có: \(3\left(2x-1\right)\left(3x-1\right)-\left(2x-3\right)\left(9x-1\right)=0\)
\(\Leftrightarrow3\left(6x^2-2x-3x+1\right)-\left(18x^2-2x-27x+3\right)=0\)
\(\Leftrightarrow18x^2-15x+3-18x^2+27x-3=0\)
hay x=0
9x2 - 1 = 3( 3x - 1 )
⇔ ( 3x - 1 )( 3x + 1 ) - 3( 3x - 1 ) = 0
⇔ ( 3x - 1 )( 3x + 1 - 3 ) = 0
⇔ ( 3x - 1 )( 3x - 2 ) = 0
⇔ 3x - 1 = 0 hoặc 3x - 2 = 0
⇔ x = 1/3 hoặc x = 2/3
thx bạn nha